Molecular cancer prevention: Current status and future directions. (18th August 2015) - Maresso, Karen Colbert; Tsai, Kenneth Y.; Brown, Powel H.; Szabo, Eva; Lippman, Scott; Hawk, Ernest T.
<x xml:space="preserve">Abstract</x> Answer questions and earn CME/CNE The heterogeneity and complexity of advanced cancers strongly support the rationale for an enhanced focus on molecular prevention as a priority strategy to reduce the burden of cancer. Molecular prevention encompasses traditional chemopreventive agents as well as vaccinations and therapeutic approaches to cancer‐predisposing conditions. Despite challenges to the field, we now have refined insights into cancer etiology and early pathogenesis; successful risk assessment and new risk models; agents with broad preventive efficacy (eg, aspirin) in common chronic diseases, including cancer; and a successful track record of more than 10 agents approved by the US Food and Drug Administration for the treatment of precancerous lesions or cancer risk reduction. The development of molecular preventive agents does not differ significantly from the development of therapies for advanced cancers, yet it has unique challenges and special considerations given that it most often involves healthy or asymptomatic individuals. Agents, biomarkers, cohorts, overall design, and endpoints are key determinants of molecular preventive trials, as with therapeutic trials, although distinctions exist for each within the preventive setting. Progress in the development and evolution of molecular preventive agents has been steadier in some organ systems, such as breast and skin, than in others. In order for molecular prevention to be fully realized as an effective strategy, several challenges to the field must be addressed. Here, the authors provide a brief overview of the context for and special considerations of molecular prevention along with a discussion of the results from major randomized controlled trials. CA Cancer J Clin 2015;65:345–383. © 2015 American Cancer Society.